Functional analysis of colonization factor antigen I positive enterotoxigenic Escherichia coli identifies genes implicated in survival in water and host colonization. Issue 6 (10th June 2021) - Abd El Ghany, Moataz; Barquist, Lars; Clare, Simon; Brandt, Cordelia; Mayho, Matthew; Joffre´, Enrique; Sjöling, Åsa; Turner, A. Keith; Klena, John D.; Kingsley, Robert A.; Hill-Cawthorne, Grant A.; Dougan, Gordon; et al.
Abstract : Enterotoxigenic Escherichia coli (ETEC) expressing the colonization pili CFA/I are common causes of diarrhoeal infections in humans. Here, we use a combination of transposon mutagenesis and transcriptomic analysis to identify genes and pathways that contribute to ETEC persistence in water environments and colonization of a mammalian host. ETEC persisting in water exhibit a distinct RNA expression profile from those growing in richer media. Multiple pathways were identified that contribute to water survival, including lipopolysaccharide biosynthesis and stress response regulons. The analysis also indicated that ETEC growing in vivo in mice encounter a bottleneck driving down the diversity of colonizing ETEC populations.